Prevalence and genetic diversity of Aeromonas veronii isolated from aquaculture systems in the Poyang Lake area, China - Xu, Xiandong; Fu, Huiyun; Wan, Guoyuan; Huang, Jiangfeng; Zhou, Zhiyong; Rao, Yi; Liu, Lihui; Wen, Chungen (Frontiers in Microbiology, 2022)
The area around Poyang Lake is the main aquaculture area in Jiangxi Province, China, and an important base for the supply of freshwater aquatic products. Aquaculture in the Poyang Lake area is severely threatened by diseases caused by bacterial pathogens, and Aeromonas veronii has been the main pathogen in recent years. In this paper, ERIC-PCR genotyping, virulence gene and antimicrobial resistance gene detection, and drug susceptibility tests were carried out on 46 A. veronii isolates obtained from aquaculture systems in the Poyang Lake area from 2016 to 2020. The results showed that the A. veronii strains in the Poyang Lake area had high genetic diversity, and 46 strains produced 36 ERIC genotypes. There were no geographical and temporal differences in the cluster analysis results and no dominant clones. All 13 virulence genes tested were detected, and all isolates had harbored 2 or more virulence genes, with a maximum of 12 virulence genes detected. Among the 22 antimicrobial resistance genes selected, 15 were detected; 97.8% of the isolates contained 2 or more antimicrobial resistance genes, with a maximum of 9 antimicrobial resistance genes. Drug susceptibility tests showed that some strains were resistant to a variety of traditionally effective drugs for Aeromomas, such as enrofloxacin and florfenicol. This study provides a reference for exploring the impact of aquaculture in the Poyang Lake area on public health.